Indonesia's National Resilience and Integration Amidst Global Challenges - Galang Anggar Kusuma; Ridwan Zamani Yahya (Konsultan Jurnal Ilmiah Indonesia, 2026)
Indonesia’s national resilience faces global challenges such as technological advancement, information disruption, foreign cultural penetration, and crises in the economy, health, and environment. This study analyzes the impact of these challenges on national resilience and integration through a literature review (2020–2025). The findings show that global threats affect all dimensions ideology, politics, economy, socio-culture, defense, and security and may trigger disintegration through social polarization, radicalism, development inequality, and declining national identity. The literature emphasizes the importance of strengthening Pancasila values, enhancing digital literacy, ensuring economic equity, modernizing defense, advancing diplomacy, and empowering education and civil society. In conclusion, Indonesia requires multi-stakeholder synergy and comprehensive strategies to build adaptive and sustainable national resilience.